FUZZY INFERENCE SYSTEM FOR DETECTING STUDENT MENTAL HEALTH - Nawindah, Nawindah; Lydiani, Saskia (Jurnal Ilmiah Teknologi Infomasi Terapan, 2020)
Please Mental health is needed by students in adolescence to have higher psychiatric problems for what psychologists need as a means of communication, consultation to provide solutions to the needs needed. When consulting is done directly see a psychologist without the presence of mental health symptoms detection devices. Fuzzy inference systems are used in determining the level of mental health of students. The tool used is the R language with sample data of Universitas Budi Luhur students. The results of this study explain about using the Mamdani fuzzy inference system centroid method with the rules (rules) using IF can easily discuss the mental health problems of students at a certain level.